Mathematics
SarinaMilliron683
2016-04-24 01:44:12
First answer choice a.A-3b b.A-(3B/2) c.2A-3B d.(A/3)+B second one is
ANSWERS
tud0r1ck
2016-04-24 02:25:21

2/3x - y = 6 y = 2/3x - 6 2x + 1/4y = 3 1/4y = -2x + 3 y = -8x + 12 I dont really understand the first one...the expressions I got when solving for y dont match ur answer choices =============== 2/3x - 6 = -8x + 12 2x - 18 = -24x + 36 2x + 24x = 36 + 18 26x = 54 x = 54/26 reduces to 27/13 y = -8x + 12 y = -8(27/13) + 12 y = - 216/13 + 12 y = -216/13 + 156/13 y = - 60/13 solution is : (27/13, -60/13)

ADD ANSWER